Pengaruh Motivasi Terhadap Komitmen Organisasional Pada Guru Madrasah Ibtidaiyah Islamiyah Kota Madiun - Yudha, Elit Prambara; Hasib, Fatin Fadhilah (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aimed to investigate the effect of motivation to organizational commitment of teacher. This research uses questionaire as the primary data and the samples are 67 teachers and candidates of MI Islamiyah Madiun.this research uses quantitative approach with multiple linear regression as the analysis method.Based on the findings, it obtained multiple linear regression equation : Y = -0,460 + 0,666X1 + 0,473X2. The result reveals that motivation affect positively and significantly to the organizational commitment of teachers in Madrasah Ibtidaiyah Islamiyah Madiun. It is known from the calculated F vakue of 105,532 with a significance level (probability) of 0,000. Value of the variable t test Motivator and Hygiene partial effect on organizational commitment of teacher in MI Islamiyah Madiun significance level <0,05.MI Islamiyah should maintenance motivation of teachers, especially to endure the motivator factors and improve the hygiene factors to achieve organizational commitment of teachers in MI Islamiyah Madiun.